Revitalizing Political Parties in Indonesia: Dissecting Patronage-Clientelism Dynamics vis-à-vis Political Representation - Muhammad Mutawalli; Zainal Amin Ayub; Hemen Philip Faga (CV. Era Digital Nusantara, 2023)
Abstract: This paper discusses and describes the patron-client phenomenon within political parties. One of the reasons why patron-client relations persist in political parties is that the interests of the political elite are veiled and do not prioritize the dynamic aspects of democratization of political parties as a forum for people's representation. The method used in this study is a normative juridical research method using a statutory and conceptual approach and presented in a formal way qualitative descriptive prescriptive. Data was collected using the interview method, the researcher interacted with informants who were flexible and open to obtain the data needed in this paper. The theory used in this paper is the general patron-client theory, which has developed and is influenced by the political culture within the internal political parties. The results of this study indicate that the patron-client relationship between political parties and cadres is good in the aspects of party elites and candidates legislature. Regional head candidates that occur give rise to a reciprocal relationship which has implications for the non-occurrence of democratization schemes and principles within political parties as a forum for people's representation that will fill public positions. The patron-client phenomenon includes, among other things, personal gifts, interests that are family interest or morphological and have the nuances of money interest. Purpose: To find out the forms of patron-client practices within political parties and society that give rise to reciprocal relationships that impact political polarization of representation that does not work well and is far from the principle of political party cadres as a representation of the people's will. as well as finding ideal concepts related to patterns of relations between parties, both relations between cadres, political parties and society in general. Design/Methodology/Approach: Normative juridical using the statute and conceptual approaches. Findings: The patron-client phenomenon can be caused by a lack of awareness and political education, as well as inconsistency and inadequate performance within political parties, both at the institutional level and among members of the legislature and executive. Originality/Value: Examining patronage-clientalism within the context of political parties has received limited scholarly attention. The topic of voting behaviour during general elections often revolves around patronage-clientelism. However, this study specifically examines the phenomenon of patronage-clientelism within political parties and its implications for political corruption.